Development and validation of liquid chromatography method for determination of glimepiride in presence of (Vimto®) soft drinks in rats: application to pharmacokinetics studies - Mohammed Hamad; Areej Rahhal; Wael Abu Dayyih; Eyad Mallah; Alice Abu Dayyih; Zainab Zakaria; Tawfiq Arafat (Wolters Kluwer Medknow Publications, 2019)
Context: Diet and beverages are thought to have notable effects on drugs. Recently, this relationship has received significant consideration. Aims: To develop and validate a simple, rapid, and sensitive method for the determination of glimepiride in rat serum. This will be performed using high-performance liquid chromatography-mass spectrometry (HPLC-MS/MS). Potential pharmacokinetic interactions between glimepiride and the soft drink, Vimto, will also be investigated in the serum of experimental rats. Materials and Methods: HPLC-MS/MS was constructed and clarithromycin was used as an internal standard. Results: The method was validated in terms of linearity, precision, accuracy, stability, and system suitability parameters. The method was found to be satisfactory and suitable for the determination of glimepiride. The precision of glimepiride was high (coefficient of variation, CV% <15%), the accuracy over all 3 days of validation was within the accepted criteria. Glimepiride peak serum concentration (Cmax) was 126.01ng/mL and was reached within 1h (Tmax) of administration. Mean area under curve (AUC) was 964.70ng/mL and was reached within 24h of administration. The Vimto soft drink significantly (P < 0.050) reduced glimepiride peak serum concentration to 57.87ng/mL and was reached within 2h of administration. AUC was significantly reduced to 335.04 ngFNx01h/mL (P < 0.050). Conclusion: Glimepiride pharmacokinetic parameters such as Cmax and AUC were significantly affected by the Vimto soft drink. Therefore, this study developed a simple, rapid, and sensitive method for validation and determination of the effects of soft drinks on drugs using the LC-MS/MS method.